Developing Sustainable Alternatives from Destroyed Buildings Waste for Reconstruction Projects - Zahraa Ali Jalil; Hafeth I. Naji; Mohammed Shihab Mahmood (Civil Engineering Journal, 2020)
This paper examines the huge destruction that has taken place in some cities of Iraq due to the terrorist acts in recent years that led to the destruction of many buildings. It examines some of the factors that encourage the use of residues of these buildings in reconstruction processes, especially the sustainability factor, so that some residues of these buildings can be used as substitutes for natural building materials and find a difference in terms of energy consumption in the case of using natural building materials and again in the case of using the proposed alternatives. In this study, three alternatives were used: 10% recycled fine aggregates (RFA), 100% RFA, and crushed clay brick aggregate (CCBA) to produce recycled coarse aggregates. The results obtained through the use of building information modeling (BIM) technology were compared with the actual consumption of the building in the case of reconstruction using natural building materials. The simulation results were comparable to real data. They were analyzed in terms of the energy consumption life cycle and annual carbon emissions for each alternative. The best alternative was selected from the results obtained from BIM. The best alternative was found in the use of CCBA in the production of concrete roofs and floors. His final model is that the energy consumption was five times lower than the original unit, while the results of carbon emissions were equal as for the electricity consumption decreased from 23,500 kW/h to less than 23,000 kW/h.